A multiomics approach reveals the pivotal role of subcellular reallocation in determining rapeseed resistance to cadmium toxicity - Zhang, Zhen-Hua (J Exp Bot, 2019)
Oilseed rape (Brassica napus) has great potential for phytoremediation of cadmium (Cd)-polluted soils due to its large plant biomass production and strong metal accumulation. Enhanced plant Cd resistance (PCR) is a crucial prerequisite for phytoremediation through hyper-accumulation of excess Cd. However, the complexity of the allotetraploid genome of rapeseed hinders our understanding of PCR. To explore rapeseed Cd-resistance mechanisms, we examined two genotypes, ‘ZS11’ (Cd-resistant) and ‘W10’ (Cd-sensitive), that exhibit contrasting PCR while having similar tissue Cd concentrations, and characterized their different fingerprints in terms of plant morphophysiology (electron microscopy), ion abundance (inductively coupled plasma mass spectrometry), DNA variation (whole-genome resequencing), transcriptomics (high-throughput mRNA sequencing), and metabolomics (ultra-high performance liquid chromatography-mass spectrometry). Fine isolation of cell components combined with ionomics revealed that more Cd accumulated in the shoot vacuoles and root pectins of the resistant genotype than in the sensitive one. Genome and transcriptome sequencing identified numerous DNA variants and differentially expressed genes involved in pectin modification, ion binding, and compartmentalization. Transcriptomics-assisted gene co-expression networks characterized BnaCn.ABCC3 and BnaA8.PME3 as the central members involved in the determination of rapeseed PCR. High-resolution metabolic profiles revealed greater accumulation of shoot Cd chelates, and stronger biosynthesis and higher demethylation of root pectins in the resistant genotype than in the sensitive one. Our comprehensive examination using a multiomics approach has greatly improved our understanding of the role of subcellular reallocation of Cd in the determination of PCR.